2021
DOI: 10.3390/curroncol28020111
|View full text |Cite
|
Sign up to set email alerts
|

A Canadian Prospective Study of Linkage of Randomized Clinical Trial to Cancer and Mortality Registry Data

Abstract: In a prospective study, we sought to determine acceptability of linkage of administrative and clinical trial data among Canadian patients and Research Ethics Boards (REBs). The goal is to develop a more harmonized approach to data, with potential to improve clinical trial conduct through enhanced data quality collected at reduced cost and inconvenience for patients. On completion of the original LY.12 randomized clinical trial in lymphoma (NCT00078949), participants were invited to enrol in the Long-term Innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Linkage studies have been shown to be extremely useful in research [17,18], but may come with several challenges related to technical aspects and privacy issues [5]. Moreover, the utility of the linkage may be compromised by bias from linkage errors where records cannot be linked or are incorrectly linked together [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linkage studies have been shown to be extremely useful in research [17,18], but may come with several challenges related to technical aspects and privacy issues [5]. Moreover, the utility of the linkage may be compromised by bias from linkage errors where records cannot be linked or are incorrectly linked together [3].…”
Section: Discussionmentioning
confidence: 99%
“…Date of death could not be used as a linkage variable, as discrepancies in survival data between the two databases have been noted. This is due to the EORTC dataset being frozen at the end of the data collection, whereas the NCR is a live database, and the challenges related to long-term follow-up data collection in clinical trials [17]. Given that incomplete linkage can result in biased estimates [3], the one-to-one matching of the de-identified clinical trial records had to be improved to get useful and reliable results.…”
Section: Discussionmentioning
confidence: 99%
“…A goal of CLEO is to use clinical trial and RWE for life-cycle assessment, including for building evidence to support reimbursement decisions, monitoring for appropriate technology implementation, and disinvestment away from low-value technologies [ 14 ]. The CEA is exploring the feasibility, acceptability, and benefit of a national harmonized approach to data, in which administrative and clinical trials can be shared and linked [ 15 ]. Comparison of highly correspondent patient data from administrative and CO.17 databases found that administrative data had longer follow-up and more complete data for certain cost drivers (e.g., hospitalizations) than clinical trial data, supporting the use of the proposed hybrid approach [ 16 ].…”
Section: The Potential Of Real-world Evidence (Rwe)mentioning
confidence: 99%